Measurements of tensor analyzing power in deuterium photo disintegration at the VEPP-3 storage ring; 11th Advanced Research Workshop on High Energy Spin Physics (DUBNA-SPIN-05), Dubna, 27 September - 1 October 2005 - Toporkov D. K.; Arenhovel H.; Barkov L. M.; Belostotsky S. L.; Dmitriev V. F.; Dyug M. V.; Gilman R.; Grigoriev A. V.; Holt R. J.; Isaeva L. G.; de Jager C. W.; Lazarenko B. A.; et al. (2006, 2006)
В фонде НТБ ТПУ отсутствует